In Search of a Converging Cellular Mechanism in Nanotoxicology and Nanomedicine in the Treatment of Cancer. (January 2018) - Gulumian, Mary; Andraos, Charlene
Multiple applications of nanomaterials have raised concern with regard to their toxicity. With increasing research into nanomaterial safety, mechanisms involved in the toxic effects of nanomaterials have begun to emerge. The importance of nanomaterial-induced lysosomal membrane permeabilization through overloading or direct damage of the lysosomal compartment, resulting in the blockade of autophagosome–lysosome fusion and autophagy dysfunction, as well as inflammasome activation were cited as emerging mechanisms of nanomaterial toxicity. It has recently been proposed that these very mechanisms leading to nanomaterial toxicity may be utilized in nanotherapeutics. This review discusses these nanomaterial-induced mechanisms in detail and how it has been exploited in cancer research. This review also addresses certain considerations that need to be kept in mind when using nanomaterials in therapeutics.